Mitochondrial haemoglobin and ATP synthase – molecular interactions in health and disease - Ebanks, Brad (2023)
The mitochondrial ATP synthase is a fundamental enzyme to multicellular life, as it is responsible for producing the vast majority of cellular adenosine triphosphate (ATP). Its molecular structure and enzymatic function have been widely studied to date. Here I have investigated the broader range of interactions that the enzyme participates in, including with mitochondrial haemoglobin, across a range of different species and under hypoxic conditions. I have also sought to understand potential changes in the activity and expression of mitochondrial ATP synthase in the skeletal muscle mitochondria of humans with chronic obstructive pulmonary disease (COPD) in response to exercise, as well as broader changes to the mitochondrial proteome.